Brown bear occurrence along a proposed highway route in Romania’s Carpathian Mountains - Csaba Domokos; Sebastian Collet; Carsten Nowak; Ferenc Jánoska; Bogdan Cristescu (Nature Conservation)
Linear transportation infrastructure threatens terrestrial mammals by altering their habitats, creating barriers to movement and increasing mortality risk. Large carnivores are especially susceptible to the negative effects of roads due to their wide-ranging movements. Major road developments are planned or ongoing throughout the range of the Romanian brown bear (Ursus arctos) population, which is numerically the largest in the European Union. The planned A8 (Tîrgu Mureș–Iași–Ungheni) highway crosses the Romanian Eastern Carpathians on their entire width, posing a risk to the Romanian and broader Carpathian transboundary bear population. In the summers of 2014, 2017 and 2020, we surveyed an 80 km-long section of the planned highway using 68 hair traps with lure mounted in pairs along the route. We aimed to assess bear occurrence, genetic connectivity across the proposed highway and to estimate the minimum number and sex ratio of bears present in the area. With an effort of 3,519 hair trapping days (17 days / trap / session), we identified 24 individuals from the 45 collected hair samples, with a higher prevalence of female bears (male:female sex ratio of 1:1.3). We documented functional connectivity across the planned highway through parent-offspring (4 cases), full-sib (2 cases) and half-sib (24 cases) genetic relationships amongst sampled individuals. Terrain ruggedness and longitude were the most important predictors of bear occurrence from our analysis of detections at hair trap locations. Bears consistently occurred in the vicinity of the planned highway when in rugged terrain of the western section of the study area and were often detected close to human settlements (< 1 km). Even at this stage, without the A8 highway constructed, connectivity is likely already limited by the existing extensive network of settlements and restricted to a few important linkage areas still free of developments. Additional threats to bears and other wildlife in the area include poaching and large numbers of free-ranging dogs. We provide recommendations to mitigate these threats.